Symmetrical Resonance Mechanism of Elimination of Parasitic Torques of the Permanent Magnets Generator when Starting and Idling - K. V. Dobrego (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2022)
. “Sticking” and vibrations of the stator of permanent magnet generators cause their increased wear, noise; also, their operation efficiency decreases. The article theoretically considers the possibility of eliminating the starting torque and oscillation of the rotation torque of the generator with permanent magnets without load due to mutual compensation of the interaction of coils with the field of permanent magnets at a certain symmetry of this field. The mentioned pheno-menon is called pi-resonance. For the specified class of model interaction potentials of the field of permanent magnets and coils, it has been shown that full compensation occurs with a certain number of coils (Ns) and magnets (Nr), while for other combinations of {Ns, Nr} the interaction is in the nature of oscillations. The corresponding tables for various classes of potentials are given which can serve as a basis for making design decisions when developing generators. Pi-resonance more probably takes place in the case of even number of stator coils and odd number of magnets, as well as with an increase in the number of stator coils. The cases of both one-sided and two-sided arrangement of the stator relative to the rotor are considered. Numerical modelling has shown that the pi-resonance is easily destroyed if the placement of magnets or coils is inaccurate, as well as by the magnet field potential symmetry breaking. An error in the angular arrangement of the coils of 1° can result in the appearance of a significant “cogging” of the rotor with energy of the order of the interaction energy of an isolated magnet – coil pair. A distortion of the symmetry of the potential yields a result similar in scale which is equivalent to the adding of a rump function with the amplitude of 10 % of the amplitude of the symmetric periodic potential. The patterns that have been discovered can be used in the design of efficient generators with reduced level of noise and vibration.